A contextual fear conditioning paradigm in head-fixed mice exploring virtual reality - Seetha Krishnan; Can Dong; Heather Ratigan; Denisse Morales-Rodriguez; Chery Cherian; Mark Sheffield (eLife)
Contextual fear conditioning (CFC) is a classical laboratory task that tests associative memory formation and recall. Techniques such as multi-photon microscopy and holographic stimulation offer tremendous opportunities to understand the neural underpinnings of these memories. However, these techniques generally require animals to be head-fixed. Few paradigms examine contextual fear in head-fixed mice, and none use freezing—the most common measure of fear in freely moving animals—as the behavioral readout. To address this gap, we developed a CFC paradigm for head-fixed mice using virtual reality (VR). We designed an apparatus to deliver tail shocks while mice navigated a VR environment. We tested three versions of this paradigm and, in all of them, observed increased freezing, particularly on the first trial, in the shock-paired VR compared to a neutral one. These results demonstrate that head-fixed mice can be fear-conditioned in VR and exhibit context-specific freezing behavior. Additionally, using two-photon calcium imaging, we tracked large populations of hippocampal CA1 neurons before, during, and following CFC. As in freely moving mice, CA1 place cells remapped and developed narrower fields following fear conditioning. Thus, our approach enables new opportunities to study the neural mechanisms underlying the formation, recall, and extinction of contextual fear memories.